Natural Science Problem Solving in Elementary School Students Using the Project Based Learning (PjBL) Model - Nenden Latifah Ulfani Fauzia; Jajang Bayu Kelana (Universitas Pendidikan Ganesha, 2020)
This research is motivated by the low level of problem-solving in science learning in elementary schools. Also, it is known that many problems occur in science learning. The purpose of this study was to determine the scenario and implementation of science problem solving using the PjBL model, teacher and student responses, and difficulties experienced by students. The research method used is descriptive qualitative. The subjects in this study were students of grade IV with a total of 30 students consisting of 14 female students and 17 male students. The results showed that there was an increase in the quality of learning when the PjBL model was applied. Thus it can be concluded that the results of the study aimed at the scenario and learning implementation were shown by the results of the teacher's average score of 77.89% and students of 78.33% which was in the good category, the teacher's response got 82% and the student's response got 84% which was very categorized. good, as well as the difficulties experienced by students with an average of 27% found in the indicators of understanding the problem and making strategy designs.